3‐dimensional visualization of implant‐tissue interface with the polyethylene glycol associated solvent system tissue clearing method. (3rd February 2019) - Yi, Yating; Men, Yi; Jing, Dian; Luo, Wenjing; Zhang, Shiwen; Feng, Jian Q.; Liu, Jin; Ge, Woo‐Ping; Wang, Jun; Zhao, Hu
Abstract: Objectives: Dental implants are major treatment options for restoring teeth loss. Biological processes at the implant‐tissue interface are critical for implant osseointegration. Superior mechanical properties of the implant constitute a major challenge for traditional histological techniques. It is imperative to develop new technique to investigate the implant‐tissue interface. Materials and methods: Our laboratory developed the polyethylene glycol (PEG)‐associated solvent system (PEGASOS) tissue clearing method. By immersing samples into various chemical substances, bones and teeth could be turned to transparent with intact internal structures and endogenous fluorescence being preserved. We combined the PEGASOS tissue clearing method with transgenic mouse line and other labelling technique to investigate the angiogenesis and osteogenesis processes occurring at the implant‐bone interface. Results: Clearing treatment turned tissue highly transparent and implant could be directly visualized without sectioning. Implant, soft/hard tissues and fluorescent labels were simultaneously imaged in decalcified or non‐decalcified mouse mandible samples without disturbing their interfaces. Multi‐channel 3‐dimensional image stacks at high resolution were acquired and quantified. The processes of angiogenesis and osteogenesis surrounding titanium or stainless steel implants were investigated. Conclusions: Both titanium and stainless steel implants support angiogenesis at comparable levels. Successful osseointegration and calcium precipitation occurred only surrounding titanium, but not stainless steel implants. PEGASOS tissue clearing method provides a novel approach for investigating the interface between implants and hard tissue.